Guidelines for evaluating school instruction about language - Hudson, Richard (Journal of Modern Languages, 2017)
This document is a discussion paper commissioned by CLIE - the Committee for Linguistics in Education, a joint committee of the Linguistics Association of Great Britain and the British Association for Applied Linguistics. CLIE tries to make the findings of linguistics and applied linguistics more readily available to the world of education, in the belief that many of these findings are relevant and valuable. The present paper is about the linguistic education of our school chidren, in the broadest sense of "linguistic" - what children ought to know about language by the end of their school careers. The paper does not argue for the inclusion of "linguistics" as an examinable curriculum subject. That may or may not be a good idea, but it is a separate issue.